Radiographic Correlation of Skeletal Maturation Using the Stages of Dental Calcification in a Peruvian Population - César Mauricio-Vilchez; Franco Mauricio; Luzmila Vilchez; Alexandra Cadenillas; Julia Medina; Frank Mayta-Tovalino (Scientifica)
Objective. To identify the correlation between the Baccetti method of SM (skeletal maturation) and the stages of DC (dental calcification) using the Demirjian method in the Orthodontics Service of the Universidad Peruana Cayetano Heredia (UPCH) in Lima-Peru. Materials and Methods. The sample was obtained from panoramic and lateral radiographs of 200 subjects (116 women and 84 men) with ages between 9 and 17 years. Canine, premolar, and molar teeth calcification was evaluated using the Demirjian method while SM was evaluated by the cervical vertebrae with the Baccetti method. Spearman’s correlation coefficient was used to assess the relationship between the maturation of these cervical vertebrae and DC. Results. There is a high correlation between the Baccetti method of maturation of the cervical vertebrae and the stages of DC ranging from r = 0.635 to 0.774 for men and from r = 0.677 to 0.784 for women (p<0.001), the second lower molar being the one with the highest correlation (r = 0.774 in men) and the second lower premolar (r = 0.784 in women). Conclusions. Stages of DC could be used as a reliable indicator of SM.